Hydrodynamic evaluation of aortic cardiopulmonary bypass cannulae using particle image velocimetry. (January 2016) - McDonald, CI; Bolle, E; Lang, HF; Ribolzi, C; Thomson, B; Tansley, GD; Fraser, JF; Gregory, SD
The high velocity jet from aortic arterial cannulae used during cardiopulmonary bypass potentially causes a "sandblasting" injury to the aorta, increasing the possibility of embolisation of atheromatous plaque. We investigated a range of commonly available dispersion and non-dispersion cannulae, using particle image velocimetry. The maximum velocity of the exit jet was assessed 20 and 40 mm from the cannula tip at flow rates of 3 and 5 L/min. The dispersion cannulae had lower maximum velocities compared to the non-dispersion cannulae. Dispersion cannulae had fan-shaped exit profiles and maximum velocities ranged from 0.63 to 1.52 m/s when measured at 20 mm and 5 L/min. Non-dispersion cannulae had maximum velocities ranging from 1.52 to 3.06 m/s at 20 mm and 5 L/min, with corresponding narrow velocity profiles. This study highlights the importance of understanding the hydrodynamic performance of these cannulae as it may help in selecting the most appropriate cannula to minimize the risk of thromboembolic events or aortic injury.